Titania coating formation on hydrostatically extruded pure titanium by micro-arc oxidation method - Maj, Ł.; Wojtas, D.; Jarzębska, A.; Bieda, M.; Trembecka-Wójciga, K.; Chulist, R.; Kozioł, W.; Góral, A.; Trelka, A.; Janus, K.; Kawałko, J.; Kulczyk, M.; et al. (Elsevier BV, 2022)
Abstract In this work, the microstructure of titania coating fabricated on the surface of hydrostatically extruded titanium grade 4 with the use of the micro-arc oxidation method was studied. The surface topography and microstructure investigations performed with atomic force microscopy and scanning and transmission electron microscopy revealed that, by using an Na2HPO4 electrolyte, a well-adherent porous coating is produced on the top surface and side walls of the extruded rod. The distribution of chemical elements was analyzed by using energy dispersive X-ray spectroscopy. The chemical elements dissolved in the electrolyte i.e. (Na, P and O) incorporated into the coating. Sodium locates preferentially in the outer part of the coating, while phosphorus and oxygen are distributed throughout the whole coating. The most relevant finding shows that a grain refinement caused by a hydrostatic extrusion provoked an increase in density of high-angle grain boundaries (HAGB), which in turn secured the formation of a continuous amorphous layer close to the substrate. The presence of this layer compensates for the effect of anisotropic substrate, producing a comparable and homogenous microstructure with a large number of micropores.